Prolegomena to Any "Metaphysics of the Future": A Critical Appraisal of John Haught's Evolutionary Theology - Hohman, Benjamin J. (Horizons, 2019)
This article examines John Haught's proposal for a "metaphysics of the future" within his program for an evolutionary theology. After offering an overview of Haught's metaphysics and its roots in process thought, it argues that Haught's account undermines his larger goal of dialogue between science and religion by making all knowledge of reality dependent on a prior and explicitly religious experience. This critique is brought into greater relief through a comparison with the thought of Bernard Lonergan, whose epistemology and metaphysics Haught has engaged numerous times throughout his career. The final section suggests one way of reframing Haught's project that avoids these serious issues without jettisoning his important core insights.